Teachers' Resilience and Burnout in the United Arab Emirates: Teaching Through the COVID-19 Pandemic - Christopher Bryan; Antje von Suchodoletz (Gulf Education and Social Policy Review)
Abstract Many factors contributed to resilience and burnout among teachers during the COVID-19 pandemic, as educators were forced to respond quickly to unexpected and unmanageable job demands and stressors. This research investigates the factors perceived by expatriate teachers in the United Arab Emirates (UAE) that influenced resilience and burnout one year from the start of the pandemic. The study observed n = 529 expatriate teachers spread across three distinct waves of data collection as schools transitioned from online to in-person education delivery in the UAE. A series of structural equation model analyses examined the relationships between latent variables of supportive and challenge factors with outcomes of resilience and burnout. Results highlight that supportive organizational environments were directly associated with higher resilience and indirectly with lower burnout scores across all three samples. Together, the results suggest that characteristics of the organizational environment should be viewed as key influencing factors in the development of teachers' resilience. Thus, resilience interventions should go beyond individualistic approaches and include organizational factors. Additionally, education policies should prioritize creating work environments where emotional resources are available; leadership is perceived as supportive, fair, and accepting; and teachers are proud to be employed.